Central Banking in Transition Countries - Wagner, Helmut (IMF Working Papers; Working Paper, 1998)
In the 1990s, the issues of central banking and central bank independence have gained increasing attention, in part owing to the role of the future European central bank, but also owing to the emergence of transition countries and the role of central banks in these countries. The main focus of the paper is on the preconditions of disinflation and successful stability policy in transition countries, paying special attention to the institutional requirements and to the choice of nominal anchors.